2021
DOI: 10.2217/fon-2021-0621
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Laboratory Outcomes of the Solid Cancer Patients Reinfected with SARS-CoV-2

Abstract: Introduction: The objective of this study was to evaluate the clinical and laboratory outcomes of solid cancer patients who were reinfected with COVID-19. Methods: Patients who were tested negative on the Coronavirus disease 2019 (COVID-19) PCR test and those with improved clinical conditions after infection with COVID-19 were enrolled in this study. Patients who received a positive COVID-19 PCR test 28 days after the initial positive PCR test were considered as reinfected. Results: A total of 1024 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Among the remaining 47 studies under full-text reading, 28 studies were excluded. Eventually, 19 articles were included in this meta-analysis and systematic review based on the inclusion criteria [ 10 , 11 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] The literature retrieval flow chart is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Among the remaining 47 studies under full-text reading, 28 studies were excluded. Eventually, 19 articles were included in this meta-analysis and systematic review based on the inclusion criteria [ 10 , 11 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] The literature retrieval flow chart is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Our study identified a small percentage of patients (6.7%) in the treatment group with low neutralization values after the second vaccination dose compared to the non‐cancer control group. These patients would probably be at greater risk of infection, reinfection, and complications in case of infections [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally the rate of following up in intensive care unit after COVID-19 infection was high patients with malignancy in the studies. [19] While Zhang et al showed this rate as 21.6%, Yang et al found this rate as 20%. [20,21] In our study, we found that the rate of intensive care unit management of patients with after COVID-19 vaccine was %12.6 and this finding demonstrated that COVID-19 vaccination could reduce the need of intensive care unit management.…”
Section: Discussionmentioning
confidence: 97%